2009
DOI: 10.1007/s11816-009-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proline accumulation and salt stress tolerance of transgenic indica rice by over-expressing P5CSF129A gene

Abstract: D 1 -pyrroline-5-carboxylate synthetase (P5CS) is a proline biosynthetic pathway enzyme and is known for conferring enhanced salt and drought stress in transgenics carrying this gene in a variety of plant species; however, the wild-type P5CS is subjected to feedback control. Therefore, in the present study, we used a mutagenized version of this osmoregulatory gene-P5CSF129A, which is not subjected to feedback control, for producing transgenic indica rice plants of cultivar Karjat-3 via Agrobacterium tumefacien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 34 publications
3
73
1
1
Order By: Relevance
“…In the present study, it was observed that co-cultivation with 1 OD culture suspended in 5 ml of 3% liquid MS medium supplemented with 100μM AS for 1 min possibly reduced the damage to explants during Agrobacterium infection. Our results are in line with the previous findings stating that the addition of AS (100μM) during co-culture was found inevitable for successful transformation (Kumar et al 2005(Kumar et al , 2009Ashok et al 2007) as it induces vir genes, extends the host range to Agrobacterium strains, and was found necessary for rice transformation as reported in other rice cultivars (Godwin et al 1992;Hiei et al 1994;Tyagi et al 2007). The explants co-cultivated for 2 min with OD = 1 culture were proved to be optimum as an increase in the co-cultivation time will lead to overgrowth of Agrobacterium and death of the explants (Rao et al 2009) as longer exposure in the infection medium may cause hypertonic conditions which may be lethal to the explants and hence results in a low frequency of transformation.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was observed that co-cultivation with 1 OD culture suspended in 5 ml of 3% liquid MS medium supplemented with 100μM AS for 1 min possibly reduced the damage to explants during Agrobacterium infection. Our results are in line with the previous findings stating that the addition of AS (100μM) during co-culture was found inevitable for successful transformation (Kumar et al 2005(Kumar et al , 2009Ashok et al 2007) as it induces vir genes, extends the host range to Agrobacterium strains, and was found necessary for rice transformation as reported in other rice cultivars (Godwin et al 1992;Hiei et al 1994;Tyagi et al 2007). The explants co-cultivated for 2 min with OD = 1 culture were proved to be optimum as an increase in the co-cultivation time will lead to overgrowth of Agrobacterium and death of the explants (Rao et al 2009) as longer exposure in the infection medium may cause hypertonic conditions which may be lethal to the explants and hence results in a low frequency of transformation.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous reports have been published that transgenic plants overproducing Pro exhibited increased tolerance to various environmental stresses, such as freezing, high salinity, and drought (Kishor et al, 1995;Nanjo et al, 1999a;Kumar et al, 2010). On the contrary, transgenic Arabidopsis (Arabidopsis thaliana) plants with an antisense AtP5CS cDNA displayed lower Pro content and decreased tolerance to osmotic stress (Nanjo et al, 1999b).…”
mentioning
confidence: 99%
“…Padidėjęs šių junginių kiekis sukelia membranų komponentų oksidacinius procesus ir antros fo tosintezės sistemos pažeidimus (Suzuki, Mittler, 2006). Dėl įvairių biotinių ir abiotinių stresų poveikio daugelyje augalų suintensyvėja proli no sintezė bei slopinamas jo katabolizmas (Kavi Kishor et al, 2005;Less, Galili, 2008;Kumar et al, 2010;Hildebrandt et al, 2015). Didesnis prolino kiekis šalčiui atspariuose augaluose įrodo, kad ši aminorūgštis dalyvauja užsigrūdinimo procese.…”
Section: įVadasunclassified